Preparative mass spectrometry instrumentation for large native protein deposition - Fremdling, P (2023)
Electrospray-ion-beam deposition (ES-IBD) is a preparative mass spectrometry technique which produces highly purified samples of non-volatile molecules adsorbed on a surface. An ES-IBD mass spectrometer (MS) ionises the analyte, transfers it into the gas phase, removes contaminations with a mass filter in vacuum and deposits it with a controlled landing energy onto a substrate. ES-IBD coupled to microscopy can elucidate the structure of biomolecules and their assemblies. In conjunction with scanning tunnelling microscopy, glycan connectivity of oligosaccharides was revealed. For larger molecules, such as native protein complexes, efforts are underway to determine their structure and conformation by coupling ES-IBD to cryo-electron microscopy or low-energy electron holography. However, there are no instruments available dedicated to depositing large, native protein complexes controlled and efficiently. In this thesis, I have modified a commercial MS designed for the analysis of large, native protein complexes (Thermo ScientificTM Q ExactiveTM UHMR) for deposition. The modified instrument has adequate beam intensity and good landing energy control. In conjunction with electron microscopy, it was shown that the native shape of protein assemblies is retained after dehydration and deposition. I used an enzymatic assay to quantify the activity of the non-covalent protein complex alcohol dehydrogenase after deposition on a dry surface. Moreover, I developed another instrument for mass- and mobility-filtered deposition of both small and large molecules. Its atmosphere-pressure interface, the ion funnel, is optimised for high transmission and it has a continuous parallel flow ion mobility filter to enable conformation-selected deposition. Radio-frequency power switches with a flexible operation frequency permit to transmit any ion with a mass-to-charge range > 50 Th, in particular heavy ions. The basis for the development of the second MS was the detailed investigation of the transport processes within an ion funnel. I formulate a 4-step ion funnel transmission model underpinned by transmission measurements of a conventional ion funnel and ion trajectory simulations taking into account the gas flow field.